PERAN MER-C (MEDICAL EMERGENCY RESCUE COMMITTEE) INDONESIA DALAM MEMBERIKAN BANTUAN KEPADA KORBAN KONFLIK DI JALUR GAZA-PALESTINA TAHUN 2009-2014 - Fitri Juliani; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Military agression between Israelis and Palestinians has caused destruction in every aspect such as education, economic, health and etc. Therefore, a number of non-state organizations have provided vital assistance to the conflict victims in Gaza Strip, one of Non-Governental Organization that has been actively conducting humanitarian aid to the victims in Gaza Strip is MER-C which is an NGO engaged in humanitarian medical emergency, ensuring reliability,independency, and neutrality in their work. This study uses a qualitative method to describe humanitarian issue that takes place in Gaza Strip in 2009 to 2014 and to discuss the MER-C Indonesia’s progress in carrying out their roles as a humanitarian act in Gaza Strip. In order to analyse this case, this study uses Non-Governmental Organization Theory and Pluralism approach.The findings of this study resulted in several things, namely that MER-C Indonesia is a humanitarian actor and execute their roles as an executor, a catalyst, and a partner. As an executor, MER-C provides large amount of aid needed to the victims. As a catalyst, MER-C widely hold a number of activities namely holding socialization and conducting advocacy. Lastly, MER-C work on existential strategy as a partner by using information politics and building hospitals that carried out by MER-C resulting in an outstanding influence and positive impact to the government of Indonesia and to the affected area in need for relief assistance which in this case is the Gaza Strip in Palestine. Keywords : NGO, MER-C, Conflict, Humanitarian Crisis, Gaza.